Faktor-Faktor Yang Mempengaruhi Penyedia Jasa Untuk Mengikuti Tender Pekerjaan Konstruksi Di Kota Palangka Raya - Larasati; Dewantoro; Nuswantoro, Waluyo (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
In the development of Central Kalimantan, the construction sector plays a strategically significant role in providing infrastructure. In 2022, there were 2,082 registered construction companies, with 27.19% of them located in Palangka Raya City. According to data obtained from the Electronic Procurement Service (LPSE) of the Palangkaraya City Government, a total of 155 construction service procurement packages were tendered in 2023. The realization of the participation level of construction job providers and consulting services experienced a decrease compared to 2022. Data collection was conducted through questionnaire distribution and literature review. This research employed the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method for data analysis using SmartPLS 3.0 software. The results of the analysis show that the characteristics of the company, project characteristics, project documents, tender conditions, and economic conditions significantly influence and contribute greatly to influencing service providers to participate in construction job tenders.